The Effect of Beeswax Emulsion Concentration as A Coating of Arumanis Mango Toward Quality During Storage at Room Temperature - Utama, I Gede Manthika; Utama, I Made Supartha; Pudja, I.A Rina Pratiwi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The objective of this research was to study the effect of various concentrations of beeswax in the baseemulsion of 0.5% sesame oil and 0.5% lemongrass oil on the quality of Arumanis mango fruits duringstorage at room temperature (26-32oC). This study used a Completely Randomized Design (CRD) withvarious concentrations of beeswax, namely 0% as control, 1%, 2% and 3%. Quality parameters measured were physical-chemical changes consisting of weight loss, spoilage intencity, hardness, total soluble solids and total acidity, as well as sensory parameters were evaluated by 10 panelists on the preferences of aroma, color, flavor and texture of the fruit flesh. The results showed that the coating of Arumanis with different concentrations of beeswax significantly affected the quality changes during storage of the fruit at the room temperature. Coating the fruit with a concentration of 2% beeswax gave the best result in slowing the physical changes and provided the best values of the sensory preferences on aroma, color, flavor and texture of the fruit flesh during the storage of coated fruit.